2011
DOI: 10.1039/c0ob00632g
|View full text |Cite
|
Sign up to set email alerts
|

The Grob/Eschenmoser fragmentation of cycloalkanones bearing β-electron withdrawing groups: a general strategy to acyclic synthetic intermediates

Abstract: Introduction of a β-electron withdrawing group to cycloalkanones allows facile C-C bond fragmentation. The reaction has been demonstrated with a large range of ring sizes, bearing various leaving and electron withdrawing groups, and using a variety of nitrogen and oxygen containing nucleophiles (>30 examples). The application of fragmentation products to the preparation of substituted γ-lactones has been demonstrated. Mechanistic studies are reported which are suggestive of a Grob/Eschenmoser type reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 56 publications
0
3
0
1
Order By: Relevance
“…It was thus found that cyclic α-iodomethyl-β-keto esters of various ring sizes undergo nucleophile-triggered fragmentation (equation 22). 25 The researchers propose a concerted fragmentation process, as opposed to a stepwise retro-Dieckmann and elimination sequence, based on the combined weight of two kinetic observations: (1) Cyclopentanones fragment faster than cyclohexanones or cycloheptanones, consistent with the ring opening being part of the rate-determining step. (2) Iodide is a better (faster) nucleofuge than bromide or mesylate, suggesting that release of the nucleofuge is also involved in the rate-determining step.…”
Section: Fragmentation Of Acyclic Substratesmentioning
confidence: 89%
See 1 more Smart Citation
“…It was thus found that cyclic α-iodomethyl-β-keto esters of various ring sizes undergo nucleophile-triggered fragmentation (equation 22). 25 The researchers propose a concerted fragmentation process, as opposed to a stepwise retro-Dieckmann and elimination sequence, based on the combined weight of two kinetic observations: (1) Cyclopentanones fragment faster than cyclohexanones or cycloheptanones, consistent with the ring opening being part of the rate-determining step. (2) Iodide is a better (faster) nucleofuge than bromide or mesylate, suggesting that release of the nucleofuge is also involved in the rate-determining step.…”
Section: Fragmentation Of Acyclic Substratesmentioning
confidence: 89%
“…The preexisting ester functional group is likely both an asset and a liability. As Lupton postulated, 25 the ester stabilizes developing negative charge in the fragmentation transition state, resulting in a faster and more efficient bond cleavage. However, the ester presents an alternative and unproductive cyclization pathway, which perhaps explains why the hindered isopropyl ester is advantageous compared with methyl ester.…”
Section: Fragmentation Reactionsmentioning
confidence: 97%
“…Die Gegenwart des elektronenziehenden Esters scheint den Fragmentierungsmechanismus zu fördern. Diese Methode ergab zuverlässig Produkte mit fünf‐, sechs‐ und siebengliedrigen Ringen und verschiedenen elektronenziehenden Gruppen unter Verwendung von stickstoff‐ und sauerstoffhaltigen Nucleophilen 113…”
Section: Fortschritt Und Anwendungenunclassified
“…The transformation of α-chloromethyl ketone 4 to dienoic acid 1 has considerable close precedent. For example, Eschenmoser and Fray reported in 1952 that sulfonate ester 6 undergoes fragmentation to form carboxylic acid 7 in an 82% yield upon exposure to aqueous potassium hydroxide (eq ). In light of the studies reported herein and precedent cited, we consider the question of mechanism for the transformation of eq to be resolved.…”
mentioning
confidence: 99%